The role of high-dose intravenous methylprednisolone in the treatment of varicella associated thrombocytopenic purpura - Aji, Dolly Yafet; Altınkaya, Nüvit; Güler, Ayşe; Ayhan, Yusuf İzzet; Erginel, Ayten; Cenani, Asım (The Turkish Journal of Pediatrics, 1993)
Two children with varicella associated thrombocytopenia are presented. Case 1, evidencing no mucosal or parenchymal bleeding was administered prednisone 2 mg/kg/day therapy after having been put under observation for a period of one week without medical treatment. There was an increase in the platelet count during the period of therapy culminating in a return to normal on the eighth day.Case 2, who was in poor clinical condition at presentation, was treated with high-dose intravenous methylprednisolone (HIVMP) 30 mg/kg/day, resulting in the platelet count returning to a normal level (180,000/mm³) on the second day of therapy.HIVMP therapy is recommended in the treatment of life-threatening cases of thrombocytopenia because of its rapid action, limited side-effects, and its low cost.
Keywords: thrombocytopenia; purpura; varicella; platelets; methylprednisolone